Knowledge Beyond Colour Lines Towards Repurposing Knowledge Generation in South African Higher Education. - Ralarala, Monwabisi K. (Studies in Forensic Linguistics Ser., 2022)
Knowledge remains timely in education. The need for academics to contemplate its relevance, worth, use and everything in-between deems a continuous intellectual project, rather than a conundrum to be solved.